Incidence of complications following open mesh repair for inguinal hernia - Alawad, Awad; Khalil, Rashid Abd Elhalim (International Journal of Medicine, 2014)
Background: Traditional suture repair of inguinal hernia is fast giving way to routine tension-free mesh repair. In many countries, mesh repair is now more common than suture repair. Objective: To study mesh related complications in the early postoperative period in patient with inguinal hernia. Methods: This cross-sectional study was conducted at Khartoum teaching hospital. One hundred and three patients who had mesh repair for inguinal hernia were the base for this study between January and December 2011 using a structured questionnaire. Results: The mean age of the patients is 43.203 ±14.41 years (STD). There were 95.1% males (n=98) and 4.9% females (n=5). Tension-free mesh repair was done for 103 patients, 12 patients (11.3%) developed wound hematoma, another 12 patients (11.3%) developed numbness at the site of operations, 11 patients (10.7%) developed scrotal swelling, nine patients (8.7%) developed seroma and four patients (3.9%) developed neuralgia at the site of operations. Conclusion: Mesh repair of inguinal hernias is not free of complications. A larger sample size and further studies are needed to compare outcome of mesh repair in our environment more objectively with traditional inguinal hernia repair. Keywords: Inguinal Hernia; Mesh Repair; Complications.